The Carotid Choke: To Sleep, Perchance to Die? - Lee Wedlake; Marc Rowe (Universidad de León, 2012)
This is an examination of the carotid choke, also known as the "sleeper hold." We will be concerned with types of sleeper holds, what part of the neck is affected, and how. This is commonly referred to as a "blood choke." There is differentiation between blood chokes and air chokes (strangulation). This article will cover application, effects, result over short and long terms, and ramifications of drug usage and mental state. We will not include the effects of a choke on the trachea, or pressure or strikes to the back of the neck. This article is presented from two perspectives; that of a martial arts practitioner/instructor and that of a physician.